Attention towards food: Conflicting mechanisms in anorexia nervosa - Horndasch, Stefanie; Oschmann, Stephanie; Graap, Holmer; Heinrich, Hartmut; Moll, Gunther; Kratz, Oliver (Appetite, 2020)
In Anorexia nervosa (AN) attentional biases towards, as well as away from, food cues have been found using different paradigms. In the current study, adult and adolescent AN patients and control participants performed two tasks while their eye movements were recorded. The tasks involved viewing and rating: 1. Single photographs of food items; 2. Pairs of pictures consisting of one picture of high calorie and one of low calorie food. Girls and women suffering from AN rated pictures of high calorie food as more negative than control participants. In the task showing single food pictures, reduced fixation times within Regions of Interest of low calorie food were seen in AN; during the task using picture pairs, a visual attentional bias towards low calorie and away from high calorie stimuli for AN was demonstrated. There is evidence for heightened visual attentional capture by high calorie stimuli when presented alone as well as attraction of attention by low calorie stimuli when shown next to high calorie stimuli, possibly facilitated by avoidance of the latter. Different attentional mechanisms seem to be activated when only one stimulus is shown compared to when two stimuli are competing for the viewer's attention.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Adolescents; Eating disorders; Eye-tracking